Technical College Teachers in Nigeria: Issues, Problems and Challenges - Abassah, Miller (Richtmann Publishing, 2011)
This paper is centered on the problems and prospects of the technical college teacher in Nigeria it explicates therelevance of technical education programme The paper recognizes the implications of the National Policy on Education (NPE)for technical (technological) education, the new curriculum development by the National Board for Technical Education (NBTE),the changing business and technology environment, the personal, professional and public image of the technical teachers. theteachers of technology have certain peculiarities which must be taken care of. before they can effectively carry out theirprofessional roles. the paper craves the indulgence of federal and state governments as well as private organizations to supportthe technical programmes at all levels of educational system, that is, the aspect of funding, provision of infrastructure, trainingmaterials, motivation, in-service training and knowledge update among other things.